Self-Rated Smell Ability Enables Highly Specific Predictors of COVID-19 Status: A Case–Control Study in Israel. (28th December 2020) - Karni, Noam; Klein, Hadar; Asseo, Kim; Benjamini, Yuval; Israel, Sarah; Nammary, Musa; Olshtain-Pops, Keren; Nir-Paz, Ran; Hershko, Alon; Muszkat, Mordechai; Niv, Masha Y
Abstract: Background: Clinical diagnosis of coronavirus disease 2019 (COVID-19) is essential to the detection and prevention of COVID-19. Sudden onset of loss of taste and smell is a hallmark of COVID-19, and optimal ways for including these symptoms in the screening of patients and distinguishing COVID-19 from other acute viral diseases should be established. Methods: We performed a case–control study of patients who were polymerase chain reaction–tested for COVID-19 (112 positive and 112 negative participants), recruited during the first wave (March 2020–May 2020) of the COVID-19 pandemic in Israel. Patients reported their symptoms and medical history by phone and rated their olfactory and gustatory abilities before and during their illness on a 1–10 scale. Results: Changes in smell and taste occurred in 68% (95% CI, 60%–76%) and 72% (95% CI, 64%–80%) of positive patients, with odds ratios of 24 (range, 11–53) and 12 (range, 6–23), respectively. The ability to smell was decreased by 0.5 ± 1.5 in negatives and by 4.5 ± 3.6 in positives. A penalized logistic regression classifier based on 5 symptoms had 66% sensitivity, 97% specificity, and an area under the receiver operating characteristics curve (AUC) of 0.83 on a holdout set. A classifier based on degree of smell change was almost as good, with 66% sensitivity, 97% specificity, and 0.81 AUC. The predictive positive value of this classifier was 0.68, and the negative predictive value was 0.97. Conclusions: Self-reported quantitative olfactory changes, either alone or combined with other symptoms, provide a specific tool for clinical diagnosis of COVID-19. A simple calculator for prioritizing COVID-19 laboratory testing is presented here. Graphical Abstract: